The interoceptive hippocampus: Mouse brain endocrine receptor expression highlights a dentate gyrus (DG)-cornu ammonis (CA) challenge-sufficiency axis. - Richard Lathe; Sheena Singadia; Crispin Jordan; Gernot Riedel (PLoS ONE, 2020)
The primeval function of the mammalian hippocampus (HPC) remains uncertain. Implicated in learning and memory, spatial navigation, and neuropsychological disorders, evolutionary theory suggests that the HPC evolved from a primeval chemosensory epithelium. Deficits in sensing of internal body status ('interoception') in patients with HPC lesions argue that internal sensing may be conserved in higher vertebrates. We studied the expression patterns in mouse brain of 250 endocrine receptors that respond to blood-borne ligands. Key findings are (i) the proportions and levels of endocrine receptor expression in the HPC are significantly higher than in all other comparable brain regions. (ii) Surprisingly, the distribution of endocrine receptor expression within mouse HPC was found to be highly structured: receptors signaling 'challenge' are segregated in dentate gyrus (DG), whereas those signaling 'sufficiency' are principally found in cornu ammonis (CA) regions. Selective expression of endocrine receptors in the HPC argues that interoception remains a core feature of hippocampal function. Further, we report that ligands of DG receptors predominantly inhibit both synaptic potentiation and neurogenesis, whereas CA receptor ligands conversely promote both synaptic potentiation and neurogenesis. These findings suggest that the hippocampus acts as an integrator of body status, extending its role in context-dependent memory encoding from 'where' and 'when' to 'how I feel'. Implications for anxiety and depression are discussed.